2018 IEEE Conference on Dependable and Secure Computing (DSC) 2018
DOI: 10.1109/desec.2018.8625124
|View full text |Cite
|
Sign up to set email alerts
|

MOSQUITO: Covert Ultrasonic Transmissions Between Two Air-Gapped Computers Using Speaker-to-Speaker Communication

Abstract: In this paper we show how two (or more) airgapped computers in the same room, equipped with passive speakers, headphones, or earphones can covertly exchange data via ultrasonic waves. Microphones are not required. Our method is based on the capability of a malware to exploit a specific audio chip feature in order to reverse the connected speakers from output devices into input devices -unobtrusively rendering them microphones [29]. We discuss the attack model and provide technical background and implementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 29 publications
(62 reference statements)
0
29
0
Order By: Relevance
“…In this approach behavioral analysis, machine learning, and anomaly detection techniques may be used to detect the presence of covert channels and raise alerts. As noted in previous work on this topic, such forms of behavioral detection inherently suffer from high false positive rates [50], [68], [65].…”
Section: B Exfiltrationmentioning
confidence: 93%
See 2 more Smart Citations
“…In this approach behavioral analysis, machine learning, and anomaly detection techniques may be used to detect the presence of covert channels and raise alerts. As noted in previous work on this topic, such forms of behavioral detection inherently suffer from high false positive rates [50], [68], [65].…”
Section: B Exfiltrationmentioning
confidence: 93%
“…1) Ultrasonic (speaker-to-speaker communication): In many IT environments desktop computers are not equipped with microphones. To overcome this limitation, Guri et al presented MOSQUITO [65] a malware that covertly turns headphones, earphones, or simple earbuds connected to a PC into a pair of microphones, even when a standard microphone is not present. Using this technique they established so-called speaker-to-speaker ultrasonic communication between two or more computers in the same room.…”
Section: F Acousticmentioning
confidence: 99%
See 1 more Smart Citation
“…The aforementioned ultrasonic covert channels are relevant to environments in which the computers are equipped with both speakers and microphones, a less common setup in many secure environments. To overcome this limitation, Guri et al presented MOSQUITO [41] a malware that covertly turns headphones, earphones, or simple earbuds connected to a PC into a pair of microphones, even when a standard microphone is muted, taped, turned off or not present. Using this technique they established so-called speaker-to-speaker ultrasonic communication between two or more computers in the same room.…”
Section: E Acousticmentioning
confidence: 99%
“…This research showed how to utilize computer fans and hard disk drive actuator arms to generate covert sound signals. In 2018, Guri et al introduced MOSQUITO [15] malware that covertly turns speakers connected to a PC into a pair of microphones. Using this technique they established socalled speaker-to-speaker air-gap communication between two computers in the same room via ultrasonic waves.…”
Section: A Electromagnetic Magnetic Acoustic and Thermalmentioning
confidence: 99%